Examining the challenges encountered by community health workers and empowering them to address mental health disorders: A qualitative study in Indonesia - Rizki Fitryasari; Marthoenis Marthoenis; Sri Warsini; Kim Usher; Hanik Endang Nihayati; Winda Kusumawardani; Hasmila Sari (International Journal of Nursing Sciences)
Objectives: Addressing the issue of mental health disorders in the community is a significant challenge for Indonesia’s healthcare professionals. This study aimed to explore the challenges that community health workers (CHWs) encounter while providing mental health services in the community. Methods: Forty CHWs were selected to participate in the study by purposive sampling method from July to August 2023 in seven primary health centers (PHCs) among three cites of Indonesia. Focus group discussions were used to collect data. All of data were analyzed using the interpretive phenomenological analysis method. Results: Considering the participants’ voluntary CHW role, the results were organized into five themes. These comprised two themes of challenges—family stigma and limited understanding of mental disorders, and three themes regarding efforts to overcome the challenges—maintaining self-motivation, fostering self-efficacy, and using communication skills when approaching families and patients. Conclusions: Upskilling and empowering CHWs helps to enhance community mental health. Thus, it is crucial to support CHWs through training programs that aim to improve mental health literacy and communication skills and diminish family stigma.